Biotransformation of Natural Products and Phytochemicals: Metabolites, Their Preparation, and Properties - Valentová, Kateřina (International journal of molecular sciences, 2023)
The term "biotransformation" refers to the process by which various compounds are biocatalyzed and enzymatically modified, as well as the metabolic changes that occur in organisms as a result of exposure to xenobiotics [...].
Keywords: Xenobiotics; biotransformace; Phytochemicals; Biotransformation; xenobiotika; fytonutrienty; Biological Products; biologické přípravky